Evaluation of the carbon footprint of the Study and Information Centre of the University of Szeged - László Gyarmati (Universitas Diponegoro, 2022)
Measuring the CO2 emission to the atmosphere has become significantly important due to the monitoring demand of pollutant emission based on the directives of the Kyoto Protocol. The carbon quota system has created strict regulations for measuring the CO2 emission in certain industries, internalizing the negative external effect of pollution created by human activity. As the built infrastructure is responsible for 40% of CO2 emission, this study focuses on the evaluation of the carbon footprint of the Study and Information Centre, which is one of the largest and most frequently visited main buildings of the University of Szeged [1]. The data collection used for the evaluation was conducted in the first quarter of 2020 and contains information for all three scopes (fuel combustion, company vehicles, fugitive emission – purchased electricity, heat and steam – purchased goods and services, business travel, waste disposal, transportation, investments). In the process of data collection, the eating habits, selective waste collection and travelling methods were covered in a visitor/employee survey as well. The results highlighted in this paper will provide a basis for further carbon reduction investments, protocols and events held for shaping the visitors’ and employees’ consciousness after the COVID 19 pandemic. Keyword: Environmental impact, carbon footprint, Bilan Carbone, higher education, travel, meals